Urgensi Kematangan Spiritual Terhadap Kesehatan Otak - Rovi Husnaini; Adnan Adnan; Chyril Futuhana Ahmad (Syifa al-Qulub, 2021)
The study of spirituality seems never to stop giving humans an understanding of the concept of self and divinity. Discussions about spirituality entered a crucial period marked by the success of science and technology in revealing non-rational secrets that were difficult to solve in the past. This paper aims to discover the importance of spiritual maturity on brain health. This research approach is qualitative with the technical method is literature study. This study indicates that researchers still have not recognized the importance of spiritual maturity essential for brain health. However, the interest of scientists on this issue is increasing and getting various responses from various groups.